The Research of the Engine-Reducer Assembly in the Traction Transmi̇Ssi̇on System - Ayaz Abdullaev; Ilham Huseynov; Israil Elyazov; Elchin Yusifzade; Ramin Abdullaev; Allahverdi Sharifov (Communications)
During the movement of the train in various operational regimes, a series of deficiencies arise in the mechanical components, which depend on kinematic and parametric factors affecting the working conditions of the traction drive. An innovative traction drive is discussed in this article, which prevents the non-uniform distribution of parametric factors, as well as dissipative, inertial, and elastic characteristics along the length of the track.